1991
DOI: 10.1128/mcb.11.9.4599
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of premature termination in c-myc during transcription by RNA polymerase II in a HeLa nuclear extract.

Abstract: Transcriptional regulation of the human c-myc gene, an important aspect of cellular differentiation, occurs in part at the level of transcript elongation. In vivo, transcriptional arrest, due to either pausing or termination, occurs near the junction between the first exon and first intron and varies with the growth state of the cell. We have tested the transcription of c-myc templates in HeLa nuclear extracts. We did not observe significant arrest under standard conditions, but we found that a considerable fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
0

Year Published

1992
1992
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 34 publications
(51 reference statements)
1
29
0
Order By: Relevance
“…Transcriptional pausing at specific DNA sequences was greater in a system in which nascent RNA chains were elongated on purified RNA polymerase II transcription complexes after chromatin re-662 constitution (Izban and Luse, 1991). Premature transcriptional termination on c-myc templates was also observed in in vitro transcription reactions using HeLa cell nuclear extracts (London et al, 1991), with the degree of termination depending on the growth conditions of the HeLa cells from which the extracts were prepared. Mixing experiments suggested that this reflected the relative amounts of termination or antitermination factors present; such factors could be involved specifically in myc transcription or represent general transcription elongation factors.…”
Section: Regulation Of Transcriptional Elongation Within Eukaryotic Cmentioning
confidence: 81%
See 1 more Smart Citation
“…Transcriptional pausing at specific DNA sequences was greater in a system in which nascent RNA chains were elongated on purified RNA polymerase II transcription complexes after chromatin re-662 constitution (Izban and Luse, 1991). Premature transcriptional termination on c-myc templates was also observed in in vitro transcription reactions using HeLa cell nuclear extracts (London et al, 1991), with the degree of termination depending on the growth conditions of the HeLa cells from which the extracts were prepared. Mixing experiments suggested that this reflected the relative amounts of termination or antitermination factors present; such factors could be involved specifically in myc transcription or represent general transcription elongation factors.…”
Section: Regulation Of Transcriptional Elongation Within Eukaryotic Cmentioning
confidence: 81%
“…Examples include c-fos (Collart et al, 1991;London et al, 1991;Mechti et al, 1991), c-myb (Bender et al, 1987;Watson, 1988), adenosine deaminase (ADA) (Chinsky et al, 1989;Lattier et al, 1989;Chen et al, 1990Chen et al, , 1991Ramamurthy et al, 1990), and tubulin (Middleton and Morgan, 1990). An additional site of premature transcriptional termination has recently been defined between the two promoters, P1 and P2, of the c-myc gene Meulia et al, 1992;.…”
Section: Regulation Of Transcriptional Elongation Within Eukaryotic Cmentioning
confidence: 99%
“…One model would predict a major role for polymerase pausing, which is widespread in yeast and other eukaryotes (Brodsky et al 2005;Kim et al 2005;Muse et al 2007;Pelechano et al 2009) and is known to generate truncated mRNAs at a range of genes beside those involved in heat shock (Fort et al 1987;Reines et al 1987;Haley and Waterfield 1991;London et al 1991;Kash et al 1993). Under an alternative model, termination and polyadenylation sites may be regulated specifically in response to environmental change.…”
Section: Discussionmentioning
confidence: 99%
“…Bornkamm 1986;Nepveu and Marcu 1986). Although truncated c-myc transcripts with 3' ends within the first exon or intron could not be detected in mammalian cells, such transcripts are found after injection of the human or murine c-myc genes into Xenopus oocytes (Bentley and Groudine 1988) and in in vitro transcription assays (Kerppola and Kane 1988;London et al 1991). The 3' ends of the most prominent of these RNAs map to two T stretches near the exon 1/intron 1 boundary, at positions +371 and + 421 from the transcription initiation site of the major c-myc promoter (P2).…”
mentioning
confidence: 99%
“…These T-rich sequences are preceded by regions of dyad symmetry that resemble p-independent bacterial terminators (Eick and Bornkamm 1986}. Cassettes containing the dyad symmetry have been shown to function as sites of 3'-end formation and intrinsic termination when cloned downstream of some heterologous promoters (Bentley and Groudine 1988;London et al 1991). However, it has not been demonstrated formally that the 3' ends of the truncated c-myc RNAs observed in oocytes or in vitro correspond to the sites of the elongation block observed by nuclear run-on transcription assays in mammalian cells.…”
mentioning
confidence: 99%